Novel Campylobacter concisus lipooligosaccharide is a determinant of inflammatory potential and virulence - Katja Brunner; Constance M. John; Nancy J. Phillips; Dagmar G. Alber; Matthew R. Gemmell; Richard Hansen; Hans L. Nielsen; Georgina L. Hold; Mona Bajaj-Elliott; Gary A. Jarvis (Journal of Lipid Research, 2018)
The pathogenicity of Campylobacter concisus, increasingly found in the human gastrointestinal (GI) tract, is unclear. Some studies indicate that its role in GI conditions has been underestimated, whereas others suggest that the organism has a commensal-like phenotype. For the enteropathogen C. jejuni, the lipooligosaccharide (LOS) is a main driver of virulence. We investigated the LOS structure of four C. concisus clinical isolates and correlated the inflammatory potential of each isolate with bacterial virulence. Mass spectrometric analyses of lipid A revealed a novel hexa-acylated diglucosamine moiety with two or three phosphoryl substituents. Molecular and fragment ion analysis indicated that the oligosaccharide portion of the LOS had only a single phosphate and lacked phosphoethanolamine and sialic acid substitution, which are hallmarks of the C. jejuni LOS. Consistent with our structural findings, C. concisus LOS and live bacteria induced less TNF-α secretion in human monocytes than did C. jejuni. Furthermore, the C. concisus bacteria were less virulent than C. jejuni in a Galleria mellonella infection model. The correlation of the novel lipid A structure, decreased phosphorylation, and lack of sialylation along with reduced inflammatory potential and virulence support the significance of the LOS as a determinant in the relative pathogenicity of C. concisus.